StAP1 phage: an effective tool for treating methicillin-resistant Staphylococcus aureus infections - Lu, Yuwen; Lu, Yifei; Li, Baobao; Liu, Jiazhen; Wang, Lixin; Zhang, Lianyang; Li, Yang; Zhong, Qiu (Frontiers in Microbiology, 2023)
Staphylococcus aureus infection has long been a serious concern in the medical field, with methicillin-resistant S. aureus (MRSA) posing a considerable challenge to public health. Given the rising resistance of bacteria to antibiotics and the favorable biosafety and environmentally friendly properties of phages, the resurgence of phage therapy offers a promising alternative or supplementary to antibiotics. In this study, we isolated and characterized a MRSA phage named StAP1 from a Chinese hospital. Phenotypic and molecular analyses revealed its broad-spectrum characteristics, genomic background, and potential application in MRSA infection treatment. Morphological examination classified the phage as a member of the Herelleviridae phage family, displaying a typical hexagonal head and a slender fibrous tail. Genomic analysis unveiled a size of approximately 144,705 bp for the StAP1 genome, encompassing 215 open reading frames (ORFs) with a 29.7% G+C content. A phylogenetic tree demonstrated that StAP1 is situated in an independent clade. The one-step growth curve demonstrated a 20-min incubation period for the phage, with an optimal multiplicity of infection (MOI) of 0.1. Moreover, StAP1 exhibited stability across a wide range of temperatures (4–50 ℃) and pH levels (4-11). Further investigation of its broad-spectrum characteristics confirmed its ability to effectively infect 5 staphylococcal cassettes chromosomal mec (SCCmec) types found in MRSA strains, notably displaying a remarkable lysis rate of 76.7% against the prevalent ST239 strain in China. In vivo studies suggested that the area of subcutaneous abscess of mice infected with MRSA was significantly reduced after administration of StAP1, which contributed to alleviate the tissue damage and inflammation. Overall, StAP1 phage presents a broad infection spectrum and exhibits strong lytic effects on various MRSA strains, highlighting its tremendous potential as a powerful tool for MRSA infection treatment.